The (S)Pacific Effects of Sunday Morning Hockey: A Participant′s Observation - Turner, David (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1992)
This second commentary complements Dr. Tolvanen′s perspective by creating a metaphor of contemporary Canadian political issues in the guise of an analysis of a Sunday Morning Hockey league.